Recognition of Elicitors in Grapevine: From MAMP and DAMP Perception to Induced Resistance - Héloir, Marie-Claire; Adrian, Marielle; Brulé, Daphnée; Claverie, Justine; Cordelier, Sylvain; Daire, Xavier; Dorey, Stéphan; Gauthier, Adrien; Lemaître-Guillier, Christelle; Negrel, Jonathan; Trdá, Lucie; Trouvelot, Sophie; et al. (Frontiers in Plant Science, 2019)
In a context of a sustainable viticulture, the implementation of innovative eco-friendly strategies, such as elicitor-triggered immunity, requires a deep knowledge of the molecular mechanisms underlying grapevine defense activation, from pathogen perception to resistance induction. During plant-pathogen interaction, the first step of plant defense activation is ensured by the recognition of microbe-associated molecular patterns, which are elicitors directly derived from pathogenic or beneficial microbes. Vitis vinifera, like other plants, can perceive elicitors of different nature, including proteins, amphiphilic glycolipid and lipopeptide molecules as well as polysaccharides, thanks to their cognate pattern recognition receptors, the discovery of which recently began in this plant species. Furthermore, damage-associated molecular patterns are another class of elicitors perceived by V. vinifera as an invader's hallmark. They are mainly polysaccharides derived from the plant cell wall and are generally released through the activity of cell wall degrading enzymes secreted by microbes. Elicitor perception and subsequent activation of grapevine immunity end in some cases in efficient grapevine resistance against pathogens. Using complementary approaches, several molecular markers have been identified as hallmarks of this induced resistance stage. This review thus focuses on the recognition of elicitors by Vitis vinifera describing the molecular mechanisms triggered from the elicitor perception to the activation of immune responses. Finally, we discuss the fact that the link between elicitation and induced resistance is not so obvious and that the formulation of resistance inducers remains a key step before their application in vineyards.